Enhancing the Management Mechanisms of Industrial Enterprise Transformation Processes (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis investigates the improvement of mechanisms for managing transformation processes in industrial enterprises amid rapidly evolving technological and economic conditions. It emphasizes the necessity of dynamic strategic planning, agile organizational structures, digital integration, and leadership development. The study also highlights the role of human capital and innovation culture in driving sustainable change. Effective transformation requires a holistic, forward-thinking approach that ensures competitiveness and adaptability in the face of disruption.